Effect of Rice Straw Ash (RSA) as partially replacement of cement toward fire resistance of self-compacting concrete - Rafiza, Abd Razak; Chin, Yi Qin; Mohd Mustafa Al Bakri, Abdullah; Zarina, Yahya; Mokhzani Khair, Ishak; Garus, Sebastian; Nabiałek, Marcin; Warid Wazien, Ahmad Zailani; Khairil Azman, Masri; Sandu, Andrei Victor; Śliwa, Agata (Polish Academy of Sciences, 2022)
Malaysia's construction industry is experiencing rapid growth, translating into increased demand for cement. However, cement production pollutes the air to the detriment of the climate via CO2 emission, making research into a cementitious replacement in concrete a necessity. This paper details an experimental study of self-compacting concrete (SCC) with partial replacement of cement by rice straw ash (RSA), which is expected to result in environmental preservation due to the green materials being used in cement production. The physicomechanical properties of the SCC with RSA replacement were determined via its compressive strength, water absorption, self-workability, and fire resistance (residual strength after exposure to high temperatures). The proportion of RSA replacement used were 0%, 5%, 10%, 15%, 20%, and 25%, and all passed the slump flow test, except the 20% and 25% samples. The SCC samples with 15% of RSA replacement reported the highest compressive strength at 7 and 28 curing days and the highest residual strength post-exposure to high temperatures. The lowest percentage of water absorption was reported by the 15% of RSA replacement, with a density of 2370 kg/m3.